2014
DOI: 10.1111/jen.12138
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring oriental fruit moth and codling moth (Lepidoptera: Tortricidae) with combinations of pheromones and kairomones

Abstract: Experiments were conducted in North and South America during 2012–2013 to evaluate the use of lure combinations of sex pheromones (PH), host plant volatiles (HPVs) and food baits in traps to capture the oriental fruit moth, Grapholita molesta (Busck), and codling moth, Cydia pomonella (L.), in pome and stone fruit orchards treated with sex pheromones. The combination of the sex pheromone of both species (PH combo lure) significantly increased G. molesta and marginally decreased C. pomonella captures as compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(60 citation statements)
references
References 31 publications
4
54
0
Order By: Relevance
“…Here, among our various studies, the mean catch in traps was consistently higher (3–5×) in traps baited with the 2‐PH lure vs. a standard sex pheromone lure, but these means were never statistically significant. Previously, we found that a significant trade‐off with using the combination sex pheromone lure was that male catch of C. pomonella was reduced in comparison with codlemone‐baited traps (Knight, Cichon, et al., ; Knight, Basoalto, et al., ). Conversely, studies reported from Argentina and Uruguay found that C. pomonella catch was similar in traps baited with either codlemone or the 2‐PH lure.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Here, among our various studies, the mean catch in traps was consistently higher (3–5×) in traps baited with the 2‐PH lure vs. a standard sex pheromone lure, but these means were never statistically significant. Previously, we found that a significant trade‐off with using the combination sex pheromone lure was that male catch of C. pomonella was reduced in comparison with codlemone‐baited traps (Knight, Cichon, et al., ; Knight, Basoalto, et al., ). Conversely, studies reported from Argentina and Uruguay found that C. pomonella catch was similar in traps baited with either codlemone or the 2‐PH lure.…”
Section: Discussionmentioning
confidence: 98%
“…One prerequisite included in our development of new, low‐cost monitoring tools has been the manager’s ability to use any new lures in standard traps with removable sticky liners (Cichon et al., ). Development of the Ajar trap was an intermediate step that allowed bisexual monitoring using sticky liners with catches comparable to the bucket traps but with fewer nontargets to sort, but was still a cumbersome design due to the replacement of the liquid baits (Knight et al., ; Knight, Cichon, et al., ; Padilha et al., ). Our new results demonstrate that G. molesta can now be monitored with a combination of volatiles released by septa and membrane lures within standard sticky traps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas narrow variations in the ratio of the two acetates have a strong effect in male behavioral response (Baker et al, 1981;Knight et al, 2014a), males accept wide variations in the quantity of Z8-12:OH in the blend Linn and Roelofs, 1983;Linn et al, 1986), and in some locations Z8-12:OH is produced in trace amounts by females (Lacey and Sanders, 1992), or does not seem to play a role in attraction (Han et al, 2001;Jung et al, 2013). Furthermore, other alcohols affect the response of male G. molesta to the two acetates Cardé et al, 1975aCardé et al, ,b, 1979, including the sex pheromone of C. pomonella (Knight et al, 2014b), and Z8-12:OH inhibits males of closely related species (Grapholita funebrana (Treitschke) and Grapholita prunivora (Walsh)), that use a similar ratio of the Z/E acetates as G. molesta Guerin et al, 1986), so a reinvestigation of the role of alcohols in the olfactory communication of G. molesta is warranted.…”
Section: Detection Of Z8-12:ohmentioning
confidence: 90%
“…Plant volatiles infl uence insect behaviour and complement sex pheromone management (Szendrei & Rodriguez-Saona, 2010;Knight et al, 2011). This effect is particularly important under mating disruption conditions, in which plant volatiles, alone or in combination with the sex pheromone, may be more effi cient for monitoring than the sex pheromone alone (Knight et al, 2014). In this respect, it is known that plant volatiles synergize insect response to pheromones (Landolt & Phillips, 1997;Reddy & Guerrero, 2004;Deisig et al, 2014), and have the advantage of attracting both sexes, whereas sex pheromone traps attract only males.…”
mentioning
confidence: 99%